2010
DOI: 10.3109/10253891003615473
|View full text |Cite
|
Sign up to set email alerts
|

Academic stress differentially influences perceived stress, salivary cortisol, and immunoglobulin-A in undergraduate students

Abstract: Academic examination stress is reported to increase physiological and self-report measures of stress and to decrease immune functioning. Here, we investigate biochemical and self-report measures of stress, immune functioning, and academic pressures before and during a midterm examination period. Undergraduate students were asked to complete a measure of global stress, the perceived stress scale (PSS-10), and to indicate their current level of perceived stress. They also answered questions regarding specific ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 31 publications
10
46
1
2
Order By: Relevance
“…This contradicts several previous studies that found different cortisol levels between normal and AD [74][75][76][77][78] and between normal and MCI groups [78,79]. Contrarily, it supports the literature that found no correlation between cortisol level and perceived stress in different populations [80][81][82]. Whereas, in this study more MCIs were diabetic, and diabetic patients have been found to secrete higher cortisol levels [83][84][85], likewise more AD patients were on sedatives or antidepressants.…”
Section: Discussioncontrasting
confidence: 99%
“…This contradicts several previous studies that found different cortisol levels between normal and AD [74][75][76][77][78] and between normal and MCI groups [78,79]. Contrarily, it supports the literature that found no correlation between cortisol level and perceived stress in different populations [80][81][82]. Whereas, in this study more MCIs were diabetic, and diabetic patients have been found to secrete higher cortisol levels [83][84][85], likewise more AD patients were on sedatives or antidepressants.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparing these results to Kim et al (1998) s study, which reported that the perceived stress level of the adults in their twenties was 1.7 and the rate of high stress level was 6.5%, the students perceived stress level was quite high and the rate of high stress level seems fairly high. These results show the increase of the college students stress level for last 10 years and support other research (Gong & Lee, 2006;Kim, 2003;Moon & Park, 2007;Murphy, Denis, Ward, & Tartar, 2010) which reported that college students difficulties in adaptation and interpersonal relationship as well as burden of job seeking and future career due to economic downturn made them experiencing tremendous stress.…”
Section: Discussionsupporting
confidence: 76%
“…Excessive stress of college students imposes negative effects on physical and emotional dimension. Preexisting studies about college students stress found out that the more stress they experienced the more physical complaints they had (Murphy, Denis, Ward, & Tartar, 2010), as well as reporting of negative subjective health status (Oh, 2009). In addition to physical symptoms, psychological symptoms (Choi, 2003;Jimenez, Navia-Osorio, & Diaz, 2010;Jin, Oh, & Kim, 2008), behavioral symptoms including alcohol consumption (Park, Armeli, & Tennen, 2004) and obsessive-compulsive behaviors (Lee, 2004) were also increased.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to dental students, available reports point to no significant differences between salivary SIgA pre-and postexams 13 . A similar finding was reported among undergraduate students attending Biology and introduction to Psychology courses 23 .…”
Section: Introductionsupporting
confidence: 72%